Capability Of New Features From FTIR Spectral Of Cervical Cells For Cervical Precancerous Diagnostic System Using MLP Networks. - Jusman, Yessi; Sulaiman, Siti Noraini; Mat Isa, Nor Ashidi; Yusoff, Intan Aidha (2009)
The applicability and reliability of Infrared (IR) spectroscopy to distinguish normal and abnormal cells has opened this research to obtain new features from IR spectral of cervical cells to be fed into multilayered perceptrons (MLP) networks.